Indonesian version of caries management by risk assessment mobile application "SKOR GIGI” in highly educated parents - Aluditasari, Alana; Fauziah, Eva; Budiardjo, Sarworini B. (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: The Indonesian version of caries management by risk assessment (CAMBRA) is a common caries risk assessment for children aged 0–5 years. During the coronavirus disease 2019 (COVID-19) pandemic, the frequency of dental visits have decreased, making it difficult to assess the caries risk in children. Smartphones and operating systems such as Android are expected to be useful for parents to assess the caries risk of their children. The education level of parents has an impact of its use. The research about the Indonesian version of CAMBRA Android–based application in children aged 0–5 years with highly educated parents has never been done in Indonesia. Purpose: To analyze the accuracy of Android–based application "SKOR GIGI” in assessing the caries risk of children aged 0–5 years by highly educated parents. Methods: This study was conducted in kindergarten, pre-primary school, and Dental Hospital of Faculty of Dentistry Universitas Indonesia with 37 highly educated parents as participants. Participants filled out the informed consent and SKOR GIGI application. Six days later, dentists filled out the Indonesian version of CAMBRA. The results of this study were statistically tested to see the sensitivity, specificity, and the comparison between the variables. Results: The sensitivity test of SKOR GIGI application showed 96.3%, specificity 100%, positive predictive value 100%, and negative predictive value 90.9%. The comparative test with McNemar showed a p-value of 1.000, which means there is no significant difference between the caries risk assessment of children aged 0–5 years using SKOR GIGI application and the Indonesian version of CAMBRA. Conclusion: SKOR GIGI application can be used to assess the caries risk of children aged 0–5 years by highly educated parents.